(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
The paper analyzes several specific aspects that arise in the operation of domestic photovoltaic power plants (DPPPs) connected to the distribution network and that negatively affect their performance and network stability. These aspects were found experimentally and become problematic when the energy produced by the DPPP approaches its maximum capacity but is not fully consumed; instead, a significant portion should be injected into the network. The research proposed developing a method to highlight and analyze three aspects: the influence of the connection line on the distribution transformer; the influence of the own load; and the influence of other DPPPs connected on the same line. Thus, using the MATLAB-Simulink environment, the entire photovoltaic power plant (power and control parts) was modeled, along with the connection line and other components that may be present (consumers and other DPPPs). The analysis of the quantities of interest shows that this method can be used not only during the design stage but also to assess the performance of DPPPs in operation.